Numerical Study of Oxygen Dilution and Temperature Distribution of Biogas Combustion in Bluff-Body MILD Burner - M. M., Noor; Wandel, Andrew P.; Talal, Yusaf (2013)
Cleaner and more efficient combustion processes are demanded by the combustion industry due to fuel depletion and air quality issues. A numerical study of a laboratory scale combustor is reported. The numerical simulations were carried out using ANSYS Fluent 14.5. Turbulence was modelled using the realizable k–ε model. The combustion chamber is an open end cylinder with the burner mounted at the bottom of the combustor. Biogas was used as a fuel with 60% methane and 40% carbon dioxide and oxidiser used was atmospheric air and synthetic air by mixing oxygen and nitrogen. The oxygen dilution ratio was analysed at the exhaust gas recirculation (EGR) and air supply mixing area. The dilution ratio is 40% for atmospheric air and a lower ratio when the low-oxygen synthetic air was used. The temperature throughout the combustion chamber was found to be close to homogeneous. The inlet air velocity did not affect the chamber and EGR temperature. In these simulations, MILD combustion was achieved.